Put x = -3 in the given polynomial and equate it to zero as x+3 is to be a factor of the polynomial.
(-3)3 – 2 × m × (-3) + 21 = 0
-27 + 6m + 21 = 0
6m -6 = 0
6m = 6
m = 1
So for x+3 to be a factor of the given polynomial, the value of m = 1.
Rate this question :
Divide polynomialMHB - Math Part-I
For which the valMHB - Math Part-I
If x-2 and x – 1/MHB - Math Part-I
Divide the firstMHB - Math Part-I
By using factor tMHB - Math Part-I
Show that m-1 isMHB - Math Part-I
Use factor theoreMHB - Math Part-I